The Pneumatron: An automated pneumatic apparatus for estimating xylem vulnerability to embolism at high temporal resolution. (5th September 2019) - Pereira, Luciano; Bittencourt, Paulo R.L.; Pacheco, Vinícius S.; Miranda, Marcela T.; Zhang, Ya; Oliveira, Rafael S.; Groenendijk, Peter; Machado, Eduardo C.; Tyree, Melvin T.; Jansen, Steven; Rowland, Lucy; Ribeiro, Rafael V.
Abstract: Xylem vulnerability to embolism represents an important trait to determine species distribution patterns and drought resistance. However, estimating embolism resistance frequently requires time‐consuming and ambiguous hydraulic lab measurements. Based on a recently developed pneumatic method, we present and test the "Pneumatron", a device that generates high time‐resolution and fully automated vulnerability curves. Embolism resistance is estimated by applying a partial vacuum to extract air from an excised xylem sample, while monitoring the pressure change over time. Although the amount of gas extracted is strongly correlated with the percentage loss of xylem conductivity, validation of the Pneumatron was performed by comparison with the optical method for Eucalyptus camaldulensis leaves. The Pneumatron improved the precision of the pneumatic method considerably, facilitating the detection of small differences in the (percentage of air discharged [PAD] < 0.47%). Hence, the Pneumatron can directly measure the 50% PAD without any fitting of vulnerability curves. PAD and embolism frequency based on the optical method were strongly correlated ( r 2 = 0.93) for E. camaldulensis . By providing an open source platform, the Pneumatron represents an easy, low‐cost, and powerful tool for field measurements, which can significantly improve our understanding of plant–water relations and the mechanisms behind embolism. Abstract : The Pneumatron is a device based on hardware and software open sources that allows the measurement of air inside plants, generating high time‐resolution estimation of embolism vulnerability. It represents an easy, low‐cost, and powerful tool for both laboratory and field measurements.